In silico annotation of five candidate genes associated with pathogenicity in Fusarium circinatum. Issue 3 (5th February 2018) - Muñoz‐Adalia, E. J.; Fernández, M.; Wingfield, B. D.; Diez, J. J.
Summary: The Pine Pitch Canker disease caused by the pathogenic fungus Fusarium circinatum is one of the most devastating diseases in pine forests, afforestation and nurseries around the world. Despite the importance of this phytopathogen, only a little is known about the genes that drive the infection traits and the virulence factors. In this work, five candidate genes (i.e. Fcfga1, Fcfgb1, Fcac, Fcrho1 and FcpacC ) were in silico annotated using the whole genome of F. circinatum as reference. The similarity of these proposed genes at nucleotide and protein levels with genes previously described in other Fusarium species was > 90% of identity and > 90% query coverage in all cases. In addition, the gene ontology of each candidate gene was also investigated.